Clasificacion taxonomica y morfologia de la planta de yuca (Manihot esculenta Crantz) - Domínguez O., Carlos E.; Ceballos, L.F. (International Center for Tropical Agriculture, 1979)
A taxonomic classification and morphological description is given of the cassava plant: leaves, inflorescence (masculine and femenine flowers), fruit (seeds), stems (reproductive branching, lateral branches, branching produced after severe damage), roots (primary root and a description of thickened roots: shape, size, color of the peel, distribution, form of adherence to stem, internal structure) and HCN content. (CIAT)